2019
DOI: 10.3390/nu11071520
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption in Adolescents and Young Adults: Age-Specific Socio-Economic and Cultural Disparities (Belgian Food Consumption Survey 2014)

Abstract: A key issue in nutritional public health policies is to take into account social disparities behind health inequalities. The transition from adolescence toward adulthood is a critical period regarding changes in health behaviors. This study aimed to determine how consumption of four emblematic food groups (two to favor and two to limit) differed according to socio-economic and cultural characteristics of adolescents and young adults living in Belgium. Two non-consecutive 24-h dietary recalls were carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
4
39
1
1
Order By: Relevance
“…The relatively high SES of the DONALD study population may limit the generalizability of our results to the general German pediatric population [37]. Some studies showed a clear inverse association between SES and intake of sugary foods, especially SSB intake [60][61][62]. In the DONALD study, in particular, young children did not consume any SSB but instead consumed substantial amounts of fruit juices.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The relatively high SES of the DONALD study population may limit the generalizability of our results to the general German pediatric population [37]. Some studies showed a clear inverse association between SES and intake of sugary foods, especially SSB intake [60][61][62]. In the DONALD study, in particular, young children did not consume any SSB but instead consumed substantial amounts of fruit juices.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, LEBTAB [39] accounts for changes in recipes over time and allows the estimation of both total FS intake and FS intake from different food groups. Finally, a variety of covariates that have been linked to dietary sugar intake could be considered as potential confounders [61,62,67].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional research is useful for identifying specific foods and nutrients that are far from optimal, particularly poor or good dietary patterns and disparities in diet between specific subgroups of the adolescent population. We included a range of populations in this Special Issue, namely adolescents from Belgium [8], China [9], Norway [10], Poland [11] and the UK [12]. Different types of foods rather than nutrients were more likely to be reported, and the top dietary behaviours reported by all of the five cross-sectional studies were sugary drinks or foods and vegetables.…”
Section: Next Steps For Interventions Targeting Adolescent Dietary Bementioning
confidence: 99%
“…Wholegrain foods, fruit, fast food or school food and skipping breakfast were also mentioned by at least two studies. A number of factors had an impact on sugary foods and drinks; consumption of sugary drinks was reported to rise with age [11], was more common in adolescent boys [10] and more common in less educated or lower social class households [8,10]. For example, in Belgium, authors also reported that amounts of sugary drinks were around 50% higher and wholegrain foods were 50% lower in households where education was lower [8].…”
Section: Next Steps For Interventions Targeting Adolescent Dietary Bementioning
confidence: 99%
See 1 more Smart Citation